OPTIMALISASI HARTA WARISAN DALAM PENINGKATAN KESEJAHTERAAN KELUARGA: STUDI MASLAHAH ATAS PRAKTIK PRODUKTIF DI KECAMATAN MEDAN HELVETIA - Annisa Annisa; M. Jamil; Dhiauddin Tanjung (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The distribution of family inheritance in Medan Helvetia District, Medan City, North Sumatra Province is managed productively. In the practice of inheritance distribution in Indonesia, the term productive inheritance is not specifically explained in the applicable positive law. However, the Compilation of Islamic Law (KHI) in optimizing inheritance as a means of empowering the family economy towards inheritance in the form of productive objects recommends an agreement between the heirs and also to maintain the substance or form (like heirlooms) and share the benefits or advantages to the heirs. This study will analyze how to manage assets productively in families in Medan Helvetia District, Medan City, North Sumatra Province from a maslahah perspective and its effectiveness in improving the welfare of heirs. The research in this thesis is a field research. This research is descriptive analytical with an empirical approach. Data collection techniques are by observation, interviews and documentation. After the data is collected, the author analyzes it qualitatively descriptively using the maslahah theory and legal effectiveness. The results of this study indicate that productive inheritance management in families in Medan Heltevia is an effort to realize family welfare that has productivity, economic and long-term investment values and an effort to prevent families from economic weakness. Productive inheritance management that is managed well and professionally can provide the greatest possible welfare to heirs, protect valuable assets in the long term, and create economic opportunities for their descendants.